AKURASI AWAL WAKTU SALAT ZUHUR DENGAN BAYANG-BAYANG MATAHARI - Hasna Tuddar Putri; Evizariani (UIN ALAUDDIN MAKASSAR, 2024)
The concept in determining noon prayer time is an explanation or theory that discusses the noon prayer time either astronomy or fiqh. In reality the position of the sun plays an important role in the accuracy of the prayer times. Which is determined by manual or digital concepts by reckoning and rukyat. In sharia law determining the time for the noon prayer is carried out when the sun goes down. To see the position of the sun's shadow has slipped or not, it is necessary to make direct observations. Therefor, it is necessary to explain again the position of the sun's shadow at noon time. It can determine the accuracy of the noon prayer time. So that there is a balance between reckoning and rukyat. This research is a qualitative research. The primary data used is the result of field research. It based on the position of the sun's shadow data. The direct data collection on the research object, the sun's shadow. After collecting data will be analyzed with an analytical descriptive method. The results is the position of the sun's shadow calculated at 12:28 WIB shows is still right on the line. It shows the north-south direction, then at 12:30 WIB the position of the sun's shadow has slipped to the east. The sun's shadow shows that in determining the noon time there must be an more 2-minute of ikhtiyat. Thus, the results will be more precise when adding ihtiyat.